Mechanotransduction in Cellular Physiology: From Cytoskeleton Dynamics to Gene Expression - Khairullah, Aswin Rafif; Furqoni, Abdul Hadi; Analianasari, Analianasari; Ansori, Arif Nur Muhammad; Wardhani, Bantari Wisynu Kusuma; Pratama, Bima Putra; Kurniasih, Dea Anita Ariani; Martindah, Eny; Utari, Fadhila; Maruf, Ilma Fauziah; Mustofa, Imam; Sukmanadi, Mohammad; et al. (Trends in Sciences, 2026)
Mechanotransduction is the process through which cells convert mechanical cues from their microenvironment into biochemical signals that regulate gene expression and cellular behavior. This review aims to critically integrate current evidence on how mechanical forces are transmitted from the extracellular matrix through adhesion complexes and cytoskeletal structures to the nucleus, thereby shaping transcriptional regulation. The discussion focuses on the coordinated roles of cytoskeletal dynamics and mechanosensitive signaling pathways, including YAP/TAZ, MRTF-A, and RhoA/ROCK, in controlling cellular proliferation, differentiation, and tissue adaptation. The physiological relevance of these mechanisms is examined in key biological contexts such as stem cell lineage specification, skeletal muscle adaptation to mechanical loading, and endothelial regulation under hemodynamic forces. In parallel, the review addresses how disruptions in mechanotransduction contribute to disease pathogenesis, particularly in cancer, fibrosis, and atherosclerosis, where altered mechanical environments lead to aberrant gene regulatory responses. Finally, this article highlights emerging methodological advances, including three-dimensional culture systems, organ-on-chip platforms, and integrated multi-omics approaches, as essential tools for improving mechanobiological modeling and identifying novel therapeutic targets related to mechanically driven cellular dysfunction. HIGHLIGHTS Cytoskeletal force routing through LINC alters chromatin and YAP/TAZ-MRTF pathways. The stiffness of the extracellular matrix influences stem cell differentiation and regulates tissue adaptability. FAK/Src and RhoA/ROCK combine adhesion signals with contractility. Dysregulation of mechanotransduction promotes cancer, fibrosis, and atherogenesis. AFM, TFM, 3D organ-on-chip technology, and multi-omics facilitate quantitative mapping. GRAPHICAL ABSTRACT